Refugees' Spatial Identity And The Reconceptualisation Of Home In Christy Lefteri's The Beekeeper Of Aleppo - Zaidi, Moufida; Salama, Raghad (The Journal of Studies in Language, Culture, and Society, 2025)
This study investigates how the social identity of refugees is affected by forced displacement while emphasizing the contributions bestowed by refugee studies upon policy-making and integration frameworks. This research delves into the obstacles that derive from physical displacement and social alienation by analyzing Christy Lefteri's The Beekeeper of Aleppo (2019) through spatial criticism and social identity theories. The study relies on Henri Lefebvre's theory of space, Homi Bhabha's concepts of (un)homeliness, Pierre Bourdieu's theory of social space, and Henri Tajfel's social identity theory in order to comprehend the displaced individual's rebuilding of their own identities. The shared practices that take place within refugee micro-communities are scrutinized through Liisa H. Malkki's concept of sedentarist bias alongside Deleuze and Guattari's philosophy of reterritorialization. This paper sheds light on the pivotal role of spatial justice during the in-between phase of displacement by identifying collective interactive rituals within the novel. Moreover, it inspects the psychological trauma, cultural fragmentation, and resilience mechanisms developed by refugees as a response to their evolving circumstances.